KAMPANYE SOSIAL STOP FATHERLESS PADA FIGUR SEORANG AYAH DI KOTA PALEMBANG - Adevia Nurhawa; Bobby Halim; Husni Mubarat (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract : Fatherless is a condition of the absence of a father both physically and psychologically in the development of a child. The statement from the minister of social affairs in 2017 regarding the fact that Indonesia is the 3rd fatherless country in the world is one of the factors behind the author in choosing this topic. The purpose of this social campaign is to provide information to fathers and prospective fathers regarding fatherless facts, the second purpose is to sensitize fathers to be maximally involved in nurturing and educating children, another goal is to help in building a harmonious family in Palembang City. The method used in this design is design thinking which consists of emphatize, define, ideate, prototype and test. The selection of media includes, board games, x banners, posters, video reels, Instagram feeds, catalogs, t-shirts, mugs, multifunctional photo frames, hats, key chains and stickers which are expected to be communicative media in helping to establish harmonious relationships between father and son in Palembang City.